MOVEMENT CAPTURE AS TECHNOLOGY TO GIVE NATURAL FLUIDITY TO MOVEMENT OF 3D CHARACTERS AND OBJECTS - Proetti, Saulo Godoy; Del Vechio, Gustavo Henrique (Revista Interface Tecnológica, 2020)
Motion capture, also called mocap, is a technology increasingly used mainly in the games and audiovisual production industry, to offer more naturalness and fluidity to the movement of objects and characters designed in 3D. This study aims to analyze how this technology operates, both in computational terms, that is, in hardware and software, and in its practical application, more specifically in cinematographic productions. For that, it brings, as an example, an analysis of the film “Alita: combat angels”, in which the use of this technology provided the three-dimensional characters with greater fluidity and integration with the filming and real characters of the scenes. What is concluded, from the study, is that without the capture of movement, it would be much more difficult to obtain such realism or natural fluidity in the development of animations and three-dimensional arts.